Resolving fine electromechanical structure of collagen fibrils via sequential excitation piezoresponse force microscopy. (11th March 2019) - Jiang, Peng; Huang, Boyuan; Wei, Liyu; Yan, Fei; Huang, Xiaowei; Li, Yuhao; Xie, Shuhong; Pan, Kai; Liu, Yunya; Li, Jiangyu
Abstract: Collagen is the main protein in extracellular matrix that is found in many connective tissues, and it exhibits piezoelectricity that is expected to correlate with its hierarchical microstructure. Resolving fine electromechanical structure of collagen, however, is challenging, due to its weak piezoresponse, rough topography, and microstructural hierarchy. Here we adopt the newly developed sequential excitation strategy in combination with piezoresponse force microscopy to overcome these difficulties. It excites the local electromechanical response of collagen via a sequence of distinct frequencies, minimizing crosstalk with topography, followed by principal component analysis to remove the background noise and simple harmonic oscillator model for physical analysis and data reconstruction. These enable us to acquire high fidelity mappings of fine electromechanical response at the nanoscale that correlate with the gap and overlap domains of collagen fibrils, which show substantial improvement over conventional piezoresponse force microscopy techniques. It also embodies the spirit of big data atomic force microscopy that can be readily extended into other applications with targeted data acquisition.